Political Party Activism Of The Malay –Muslim Political Parties: UMNO And PAS Grassroots Party Activists In Terengganu - Wan Abdul Ghapar, Wan Rohila Ganti (2020)
This research explores the intensity of their activism in UMNO and PAS, and the incentives that have influenced them to become politically active since it is often taken for granted that people will only invest in political activism in exchange for some sort of benefits. This study also compares the differences of incentives that prevail among UMNO and PAS grassroots party activists.